The Phenomenology of Evil in language - Hatam Wlya Muhammad; Halmat Sardar Omar (Zanco Journal of Humanity Sciences)
The existence and non-existence of evil, as an eternal and timeless problem, are linked to the existence of mankind.  Many theories arose from the ancient times until the 20th century to explain evil, as it is complicated philosophical issues. A Secular and contemporary framework of evil was not formed until the eighties of the last century which viewed man as the doer of evil actions and also recognized language related evil actions that have harmful and negative impacts. By settling the defects of the ontological and moral treatments of wickedness, (Claudia Card) was able to formulate a phenomenological and moral theory of evil that defines it as a human act that has negative impacts, and is committed intentionally as a harmful mistake by a drive that bears responsibilities. In philosophical thoughts phenomenology is a relatively new scheme that was established by (Husserl) in the first half of the twentieth century, that focuses on objective research on mental phenomena of human actions that can be sensed through their effects.